Driven to Darkness : Jewish Emigre Directors and the Rise of Film Noir - Brook, Vincent, 1946- (Book collections on Project MUSE., 2009)
Driven to Darkness explores the influence of Jewish TmigrT directors and the development of this genre. While filmmakers such as Fritz Lang, Billy Wilder, Otto Preminger, and Edward G. Ulmer have been acknowledged as crucial to the noir canon, the impact of their Jewishness on their work has remained largely unexamined until now. Through lively and original analyses of key films, Vincent Brook penetrates the darkness, shedding new light on this popular film form and the artists who helped create it.